A string-wise CRDT algorithm for smart and large-scale collaborative editing systems. (August 2017) - Lv, Xiao; He, Fazhi; Cai, Weiwei; Cheng, Yuan
Abstract: With the development of big data and cloud computing, real-time collaborative editing systems have to face new challenges. How to support string-wise operations for smart and large-scale collaborations is one of the key issues in next generation of collaborative editing systems, which is both the core topic of collaborative computing area and the fundamental research of many collaborative systems in science and engineering. However, string-wise operations have troubled the existing collaborative editing algorithms, including Operational Transformation (OT) and Commutative Replicated Data Type (CRDT), for many years. This paper proposes a novel and efficient CRDT algorithm that integrates string-wise operations for smart and massive-scale collaborations. Firstly, the proposed algorithm ensures the convergence and maintains operation intentions of collaborative users under an integrated string-wise framework. Secondly, formal proofs are provided to prove both the correctness of the proposed algorithm and the intentions preserving of string-wise operations. Thirdly, the time complexity of the proposed algorithm has been analyzed in theory to be lower than that of the state of the art OT algorithm and CRDT algorithm. Fourthly, experiment evaluations show that the proposed algorithm outperforms the state of the art OT algorithm and CRDT algorithm.